Sosialisasi Pendidikan Menciptakan Suasana Sekolah Tanpa Kekerasan: Be Real Friends and Stop Bullying - Nasution, Ahmad Faisal; Panggabean, Nurul Huda; Situmorang, Nurbaity; Kairani, Anita (Puslitbang Sekawan Institute Nusa Tenggara, 2025)
Bullying is a serious problem in the world of education that hurts the psychological, social, and academic development of students. Prevention efforts through educational socialization are important in fostering mutual awareness to create a safe and comfortable learning environment. This educational socialization aims to evaluate the effectiveness of socialization Activities to promote a non-violent school environment: Be Real Friends and Stop Bullying by involving 50 participants, consisting of teachers, lecturers, students, and students in North Sumatra Province. The method used was quantitative descriptive with instruments in the form of a questionnaire on the benefits of socialization and a test of participants' material comprehension (post-test). The results showed that all participants responded positively to the socialization activities, with 58.3% strongly agreeing and 41.7% agreeing on its benefits. Additionally, the post-test results showed an enhancement in material comprehension, where 63.6% of participants were categorized as excellent, 32.7% as good, and only 3.6% as fair. Thus, the socialization of bullying prevention education has proven to be effective in strengthening participants' awareness and understanding of the impact and strategies of bullying prevention. This program could serve as a preventive intervention model in schools and universities and was recommended for continuous implementation to strengthen an educational culture free from bullying.